Analysis of the relationship between contingency factors and management accounting practices adopted in the light of contingency theory: a study in hotels in the municipalities of Recife and Ipojuca in the state of Pernambuco - Sobrinho, Samara Lima (2025)
Purpose: The objective of this study is to analyze the relationship between contingency factors and management accounting practices adopted by hotels located in the municipalities of Ipojuca and Recife, in the state of Pernambuco. Methodology: This research is characterized as exploratory-descriptive. For its development, a survey-type survey was carried out. Data collection took place from October 14, 2019 to January 3, 2020. Data analysis was carried out in two stages, namely: the first consisted of performing descriptive statistics and the second stage occurred by applying the test non-parametric Spearman correlation coefficient. Results: The results showed that the practices most used by hotel managers are: a) separation of fixed and variable costs; b) cost assessment of service quality; c) analysis of the cost/volume/profit relationship; d) analysis of the profitability of the service; e) creating a budget to control costs; and f) creating a budget for planning. Regarding the analysis of the relationship between contingency factors (environment, technology, size, structure and strategy), all of them showed at least one statistically significant correlation with some management accounting practice, highlighting the technology and environment factors which were those that presented the highest number of correlations with management accounting practices. Contributions of the Study: The results of this research contribute to the advancement of the debate involving management accounting practices and contingency factors based on results obtained in an important Brazilian economic sector. The results of this study can also be used by managers who seek to mitigate the possible impacts generated by contingencies imposed by the hotel sector, especially technology and performance evaluation.